Guidance manual : - Lee, Henry (Environmental Protection Agency, 1989)
The recommendations in this document are based on our experience and best scientific judgment. It is our hope that the "routine" and experimental sediment bioaccumulation tests, as well as aid regulators in determining when bioaccumulation tests are needed, in evaluating the QA/QC procedures of such tests, and in interpreting the results.